Out with the old and in with the new? Investigating competition between Barred Owls (Strix varia) and Northern Spotted Owls (Strix occidentalis caurina) in northwestern California with a playback experiment - Van Lanen, Nicholas J., author; Franklin, Alan B., advisor; Noon, Barry R., committee member; Reiser, Raoul Frederick, II, committee member; Huyvaert, Kathryn P., committee member (Colorado State University. Libraries, 2010)
The Northern Spotted Owl (Strix occidentalis caurina) is a controversial species in the Pacific Northwest that is listed as threatened under the Endangered Species Act. The Barred Owl (Strix varia), a species historically restricted to eastern North America, has recently expanded its range to completely overlap that of the Northern Spotted Owl. Recent evidence suggests that Barred Owls may displace Northern Spotted Owls from their territories. The focus of my study was to determine whether Barred Owls have the potential to competitively exclude Northern Spotted Owls from their territories. I used a playback experiment to observe and quantify aggressive vocal and physical behavior of Barred and Northern Spotted Owls during territorial defense. Trials consisted of displaying a Northern Spotted or Barred Owl taxidermy mount, and broadcasting recorded vocalizations of the corresponding species, in both Barred and Northern Spotted Owl territories. The frequency and intensity of residents' responses to playbacks were digitally recorded as was the acceleration experienced by the mount's head during physical attacks by the residents. When agonistic interspecific interactions occurred in this study I found that Barred Owls responded with higher levels of vocal and physical aggression than Northern Spotted Owls. However, the frequency of interspecific interactions was lower compared to intraspecific interactions among Northern Spotted Owls alone. This study suggests that Barred Owls are likely to assume the dominant role during interspecific interactions with Northern Spotted Owls and indicates that competitive exclusion is a plausible mechanism by which Barred Owls could contribute to the observed population declines of Northern Spotted Owls in areas of co-occurrence.
Department Head: Kenneth Ray Wilson.